CuBDC nanosheet as well as preparation method and application thereof
By using a thin film reactor in the preparation of CuBDC nanosheets, the reaction interface and reaction rate are controlled, and the problems of nanosheet layer thickness and low aspect ratio in the prior art are solved, and a single layer CuBDC nanosheet is efficiently prepared, with high aspect ratio and large specific surface area, which is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202311134379.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-05
AI Technical Summary
In the existing preparation methods of CuBDC nanosheets, it is difficult to control the morphology and reaction rate of the crystal nucleus, resulting in thick nanosheet layers, low aspect ratio, incomplete reactions, and low yields.
Using a thin film reactor, copper ion solution is dropped into the ligand solution through thin film components, the reaction is controlled at the interface of the microporous film, the binding rate of metal ions and ligands is delayed, and the two-dimensional morphology of the crystal is regulated, and a single layer 2D MOF nanosheet with uniform morphology and controllable length and aspect ratio is obtained.
A single-layer CuBDC nanosheet has been achieved, with high aspect ratio and large specific surface area, and is suitable for gas storage, adsorption and separation, heterogeneous catalysis, electrochemistry and analysis fields. It has a simple preparation method, low material, low cost, high yield, and easy to prepare in large quantities.
Smart Images

Figure CN119570044A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano materials, and specifically relates to a CuBDC nano sheet and a preparation method and application thereof. Background Art
[0002] Metal-organic frameworks (MOFs) are organic-inorganic hybrid porous crystalline materials composed of metal ion centers and organic ligands. Two-dimensional (2D) MOF nanosheets are anisotropic MOFs with two-dimensional layered structures, which have ultra-thin sheet thickness, good solubility and dispersibility, excellent photoelectric properties, and easy functionalization of pore surfaces. Compared with traditional isotropic MOFs, they not only have the characteristics of porosity and adjustable pore size, but also have the advantages of long-range order and anisotropy of crystalline materials, high porosity, and large specific surface area. They are widely used in energy storage, catalysis, sensing, adsorption and separation, and other fields. 2D-MOF is a new type of material with great potential.
[0003] Copper terephthalate (CuBDC) is a typical 2D MOF with a regular lamellar structure, which has been reported in many literatures. Although the morphology and properties are excellent, the synthesis steps are difficult to control and reproduce. Only by accurately controlling the solution concentration and reaction rate of metal ions and ligands can two-dimensional nanosheets with excellent morphology be obtained. At present, most of the CuBDC nanosheets synthesized in the literature are not single-layer and need secondary treatment, or have low aspect ratio.
[0004] CN106252663B discloses a method for preparing CuBDC nanosheets: the first step is to weigh copper nitrate solid and p-dibenzoic acid solid, and mix them with organic solvents acetonitrile and N,N-dimethylformamide; the second step is to heat the mixture obtained in step one in a water bath and stir; the third step is to put the solution obtained in step two into an oven and dry it to obtain a metal organic framework material CuBDC nanosheet. The method described in the invention directly dissolves the Cu salt into the solvent, the initial crystal nucleus is formed relatively quickly, the morphology of the crystal nucleus is difficult to control, the obtained CuBDC nanosheets are stacked, difficult to peel off, and the morphology is poor. The method adopts conventional heating methods such as water baths, the crystal growth process takes a long time, and the efficiency and yield are low.
[0005] CN114288879A discloses a method for preparing two-dimensional CuBDC-NH2: the first step is to add anhydrous copper acetate to a mixed solution A to dissolve, thereby obtaining an anhydrous copper acetate solution; the second step is to add 2-aminoterephthalic acid to a mixed solution B to dissolve, thereby obtaining a 2-aminoterephthalic acid solution; the third step is to spray the anhydrous copper acetate solution into the 2-aminoterephthalic acid solution through an ultrasonic spray device, and let it stand to obtain a solid substance, and the solid substance is washed and filtered to obtain a two-dimensional CuBDC-NH2 solid. The ultrasonic spray device used in the invention still uses a feeding method of macroscopic droplets, and the control effect on the metal precursor is relatively limited. The crystal nucleus formation process and the product structure are still difficult to control. The resulting CuBDC nanosheets are severely agglomerated, the sheet thickness is large, easy to stack, and the aspect ratio is low.
[0006] In the current preparation method, there is no effective method to control the contact reaction rate of the metal solution and the ligand solution, and the obtained CuBDC nanosheet layer is thicker, the aspect ratio is lower, and the reaction is difficult to be complete, and the yield is low. Summary of the invention
[0007] In view of the deficiencies of the prior art, the present invention provides a CuBDC nanosheet and a preparation method and application thereof. The CuBDC nanosheet is a single layer, has a high aspect ratio, and a large specific surface area. The preparation method is simple, the material is cheap and readily available, the cost is low, and it is easy to prepare in large quantities. The CuBDC nanosheet is suitable for gas storage, adsorption separation, heterogeneous catalysis, electrochemistry, and analysis.
[0008] The first aspect of the present invention provides a CuBDC nanosheet. The CuBDC nanosheet is a single-layer two-dimensional CuBDC nanosheet material; the CuBDC nanosheet has an aspect ratio of 80 to 400, preferably 100 to 300; wherein the aspect ratio is the ratio of the length to the thickness of the nanosheet.
[0009] According to the present invention, the specific surface area of the CuBDC nanosheets is 580-630 m 2 / g.
[0010] According to the present invention, the length of the CuBDC nanosheet is 2 to 6 μm, preferably 4 to 5 μm, and the thickness is 15 to 25 nm, preferably 18 to 22 nm.
[0011] The second aspect of the present invention provides a method for preparing CuBDC nanosheets. The method comprises:
[0012] (1) The method adopts a thin film reactor; a thin film component is provided in the thin film reactor, and the reactor is divided into an upper layer area and a lower layer area by the thin film component; and a hole is provided on the thin film component;
[0013] (2) placing a copper ion solution in the upper region of a thin film reactor; placing a ligand solution in the lower region of the thin film reactor; dripping the copper ion solution into the ligand solution through the holes in the thin film component, reacting in the lower region of the reactor, and obtaining the CuBDC nanosheets after separation.
[0014] According to the present invention, in step (1), the lower region of the thin film reactor can accommodate a reaction solution including a copper ion solution and a ligand solution to allow the reaction to occur. Preferably, the volume ratio of the upper region to the lower region is 1:1 to 1:2.
[0015] According to the present invention, in step (1), the thin film reactor is provided with a liquid inlet and outlet, which are used to inject or discharge the solution.
[0016] According to the present invention, in step (1), the pores on the film component have a diameter of 3 to 5 μm and a porosity of 80% to 90%. More preferably, the pore thickness is 30 to 60 μm.
[0017] According to the present invention, in step (1), the material of the film component is at least one of polytetrafluoroethylene film, polyvinylidene fluoride film, polyvinylidene fluoride, and nylon. The film component is treated by immersing in a mixed solution of N,N-dimethylformamide:acetonitrile in a volume ratio of 1:2 to 2:1.
[0018] According to the present invention, in step (2), the copper ion solution includes an inorganic copper salt, N,N-dimethylformamide and acetonitrile. Further, based on the mass of the copper ion solution, the copper ion solution includes: 0.8% to 1.5% of inorganic copper salt, 22% to 27% of N,N-dimethylformamide, and 72% to 77% of acetonitrile. The inorganic copper salt includes one or more of copper nitrate, copper chloride, copper sulfate, copper acetate or basic copper carbonate. The solution is prepared by conventional methods.
[0019] According to the present invention, in step (2), the ligand solution includes phthalic acid, N,N-dimethylformamide and acetonitrile. Further, based on the mass of the ligand solution, the ligand solution includes: 0.8% to 1.5% terephthalic acid, 72% to 77% N,N-dimethylformamide, and 22% to 27% acetonitrile. The solution is prepared by conventional methods.
[0020] According to the present invention, in step (2), the mass ratio of the copper ion solution to the ligand solution is 0.8 to 1.2.
[0021] According to the present invention, in step (2), the copper ion solution is added dropwise for 100 to 120 minutes.
[0022] According to the present invention, in step (2), the reaction is carried out under microwave heating. The microwave heating temperature is 40-55° C., the time is 3-6 hours, the microwave heating frequency is 2000-5000 MHz, and the power is 500-1000 W. After the reaction, a blue suspended solid is obtained.
[0023] According to the present invention, in step (2), separation can be carried out by conventional solid-liquid separation methods, preferably centrifugal separation. After separation, washing and / or drying can be performed. The washing solvent is N,N-dimethylformamide and / or chloroform. The purpose of washing is to remove excess solutes and residual solvents that have not reacted completely. The drying conditions are: temperature 60-80°C time 18-24h. The drying can be vacuum drying or air atmosphere drying.
[0024] The third aspect of the present invention provides the application of the CuBDC nanosheets or the CuBDC nanosheets prepared by the preparation method in the fields of gas storage, adsorption separation, heterogeneous catalysis, electrochemistry and analysis.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] 1. The CuBDC nanosheet of the present invention is a single-layer two-dimensional CuBDC nanosheet material; the aspect ratio of the CuBDC nanosheet is 80 to 400. The CuBDC has a high aspect ratio and a large specific surface area, and is suitable for gas storage, adsorption separation, heterogeneous catalysis, electrochemistry and analysis.
[0027] 2. In the preparation method of CuBDC nanosheets of the present invention, the method adopts a thin film reactor; a thin film component is provided in the thin film reactor, and the reactor is divided into an upper region and a lower region by the thin film component; holes are provided on the thin film component; in the reactor, a copper ion solution is dripped into a ligand solution through the holes, a reaction occurs in the lower region of the reactor, and the CuBDC nanosheets are obtained after separation.
[0028] The method of the present invention adopts an interface control reactor with a microporous film as the core, and controls and delays the binding rate of metal ions and ligands by controlling the pore size of the microporous film, thereby controlling the nucleation process in the initial stage of the reaction, regulating the two-dimensional morphology of the crystal, and being conducive to obtaining a single-layer 2D MOF nanosheet crystal nucleus with uniform morphology and controllable length and aspect ratio. And due to the long-term existence of the reaction interface, the reaction can continue until the reaction is complete, so the yield is high. The present invention can obtain an ultra-thin single-layer 2D MOF nanosheet, exposing more outer surfaces and having a higher specific surface area. The materials used in the present invention are cheap and easy to obtain, the method is simple, the cost is low, the yield is high, and it is easy to prepare in large quantities. The CuBDC has a high aspect ratio and a large specific surface area, and is suitable for gas storage, adsorption separation, heterogeneous catalysis, electrochemistry and analysis fields.
[0029] 3. The CuBDC nanosheets of the present invention are suitable for gas storage, adsorption separation, heterogeneous catalysis, electrochemistry and analysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the thin film reactor in the present invention.
[0031] Among them, 1-thin film reactor, 2-liquid inlet, 3-liquid outlet, 4-upper layer area, 5-thin film component, 6-lower layer area, 7-contact reaction zone, 8-holes on the thin film component.
[0032] Figure 2 , 4 5 is a scanning electron microscope image of the length of the CuBDC nanosheet prepared in Example 1 of the present invention.
[0033] Figure 3 This is a scanning electron microscope image of the thickness of the CuBDC nanosheets prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described in detail below with reference to the accompanying drawings and through specific embodiments, but the content of the present invention is not limited to the following examples. The reagents used in the present examples are all commonly used or commercially available products in the industry unless otherwise specified.
[0035] The size of the CuBDC nanosheet of the present invention is measured by scanning electron microscope images. The aspect ratio of the present invention is the ratio of the length to the thickness of the nanosheet.
[0036] In the present invention, the BET specific surface area is measured by a Micrometrics ASAP 2460N2 adsorption instrument using a low temperature liquid nitrogen adsorption method at a temperature of 77K.
[0037] In the present invention, the scanning electron microscope adopts Zeiss Gemini Ultra-55 scanning electron microscope for testing, and the irradiation energy is 5 keV.
[0038] In the present invention, each example adopts Figure 1 The thin film reactor 1 is shown; a thin film component 5 is provided in the thin film reactor, and the reactor 1 is divided into an upper region 4 and a lower region 6 by the thin film component 5; a hole 8 is provided on the thin film component. A liquid inlet 2 and a liquid outlet 3 are provided on the thin film component for the entry or discharge of liquid. When preparing nanosheets, a copper ion solution is placed in the upper region 4, and a ligand solution is placed in the lower region 6. The copper ion solution is dripped into the ligand solution in the lower region through the hole 8 of the thin film component, and a reaction occurs in the contact reaction zone 7 in the lower region of the reactor, and the CuBDC nanosheets are obtained after separation.
[0039] In the embodiment of the present invention, the volume ratio of the upper region to the lower region of the thin film reactor is 1:1.5. The material of the thin film component is polytetrafluoroethylene. Before use, the thin film component is soaked in a mixed solution of N,N-dimethylformamide:acetonitrile = 1:1.
[0040] In the present invention, CO2 permeability means gas permeability (P), which refers to the amount of gas that passes through a unit area under a unit pressure difference per unit time. The calculation formula is:
[0041]
[0042] Among them, P i It is the gas permeability, the unit is Barrer (1Barrer = 10 -10 cm 3 (STP) cm cm -2 ·sec -1 cmHg -1 ), V is the downstream volume in cm 3 , R is the gas constant 8.314 J·mol -1 ·K -1 , T is the temperature in K, S is the effective permeation area of the membrane in cm 2 , dP i / dt is the growth rate of the downstream gas pressure over time, l is the thickness of the membrane in cm, ΔP i is the pressure difference in bar.
[0043] In the present invention, the selectivity of CO2 / CH4 means the ratio of CO2 to CH4 gas permeability, and the calculation formula is:
[0044]
[0045] Example 1
[0046] The thickness of the pores on the thin film component of the thin film reactor in this example is 30 μm, the pore diameter is 5 μm, and the porosity is 88%.
[0047] 0.5 g of copper nitrate was added to a mixed solvent of 15 g of N,N-dimethylformamide and 45 g of acetonitrile to prepare a copper ion solution.
[0048] The ligand solution was prepared by adding 0.5 g of terephthalic acid to a mixed reagent of 45 g of N,N-dimethylformamide and 15 g of acetonitrile.
[0049] According to the mass ratio of copper ion solution to ligand solution of 1:1, copper ion solution and ligand solution are respectively injected into the upper and lower regions of the thin film reactor. The copper ion solution drips into the ligand solution through the holes of the thin film component and reacts in the lower region of the reactor. The dripping time of the copper ion solution is 120 minutes. The reactor is placed in a microwave heating device with a frequency of 2500MHz and a power of 500W. The heating temperature is 55℃ and the time is 6 hours. In the middle thin film controlled reaction zone, the interface of the two solutions is controlled to contact slowly, react, and generate blue suspended solids.
[0050] The solution after the reaction was centrifuged to separate the solid and liquid, and then washed with N,N-dimethylformamide for 3 times and chloroform for 3 times. After vacuum drying at 80°C for 18 hours, CuBDC nanosheets were obtained with a yield of 78wt%.
[0051] SEM characterization shows that the single-layer nanosheets are uniform in size, with a length of 2 to 6 μm, a thickness of about 20 nm, an aspect ratio of 100 to 300, and a BET specific surface area of 580 m 2 / g.
[0052] Example 2
[0053] The thickness of the pores on the thin film component of the thin film reactor in this example is 35 μm, the pore diameter is 5 μm, and the porosity is 88%.
[0054] 0.72 g of copper sulfate was added to a mixed solvent of 12 g of N,N-dimethylformamide and 36 g of acetonitrile to prepare a copper ion solution.
[0055] A ligand solution was prepared by adding 0.9 g of terephthalic acid to a mixed reagent of 45 g of N,N-dimethylformamide and 15 g of acetonitrile.
[0056] According to the mass ratio of copper ion solution to ligand solution of 4:5, copper ion solution and ligand solution were injected into the upper and lower areas of the thin film reactor respectively. The copper ion solution dripped into the ligand solution through the holes of the thin film component and reacted in the lower area of the reactor. The dripping time of the copper ion solution was 110 minutes. The reactor was placed in a microwave heating device with a frequency of 2000MHz and a power of 500W, the heating temperature was 55℃, and the heating time was 3 hours. In the middle thin film controlled reaction zone, the interface of the two solutions controlled slow contact, reacted, and generated blue suspended solids.
[0057] The solution after the reaction was centrifuged to separate the solid and the liquid, and then washed with N,N-dimethylformamide for 3 times and chloroform for 3 times, and vacuum dried at 80° C. for 18 hours to obtain the CuBDC nanosheets of the present invention, with a yield of 70%.
[0058] SEM characterization shows that the single-layer nanosheets have uniform size, a length of 3-4 μm, a thickness of about 20 nm, an aspect ratio of 150-200, and a BET specific surface area of 585 m 2 / g.
[0059] Example 3
[0060] The thickness of the pores on the thin film component of the thin film reactor in this example is 45 μm, the pore diameter is 4 μm, and the porosity is 88%.
[0061] 0.96 g of basic copper carbonate was added to a mixed solvent of 18 g of N,N-dimethylformamide and 54 g of acetonitrile to prepare a copper ion solution.
[0062] The ligand solution was prepared by adding 0.8 g of terephthalic acid to a mixed reagent of 45 g of N,N-dimethylformamide and 15 g of acetonitrile.
[0063] According to the mass ratio of copper ion solution to ligand solution of 6:5, copper ion solution and ligand solution were injected into the upper and lower areas of the thin film reactor respectively. The copper ion solution dripped into the ligand solution through the holes of the thin film component and reacted in the lower area of the reactor. The dripping time of the copper ion solution was 100 minutes. The reactor was placed in a microwave heating device with a frequency of 3000MHz and a power of 1000W, the heating temperature was 40℃, and the heating time was 6 hours. In the middle thin film controlled reaction zone, the interface of the two solutions controlled slow contact, reacted, and generated blue suspended solids.
[0064] The solution after the reaction was centrifuged to separate the solid and liquid, and then washed with N,N-dimethylformamide for 3 times and chloroform for 3 times. After vacuum drying at 80°C for 24 hours, CuBDC nanosheets were obtained with a yield of 76%.
[0065] SEM characterization shows that the single-layer nanosheets have uniform size, length of 4-6 μm, thickness of about 25 nm, aspect ratio of 160-240, and BET specific surface area of 596 m 2 / g.
[0066] Example 4
[0067] The thickness of the pores on the thin film component of the thin film reactor in this example is 60 μm, the pore diameter is 3 μm, and the porosity is 88%.
[0068] 0.6 g of copper nitrate was added to a mixed solvent of 15 g of N,N-dimethylformamide and 45 g of acetonitrile to prepare a copper ion solution.
[0069] The ligand solution was prepared by adding 0.6 g of terephthalic acid to a mixed reagent of 45 g of N,N-dimethylformamide and 15 g of acetonitrile.
[0070] According to the mass ratio of copper ion solution to ligand solution of 1:1, copper ion solution and ligand solution were injected into the upper and lower regions of the thin film reactor respectively. The copper ion solution dripped into the ligand solution through the holes of the thin film component and reacted in the lower region of the reactor. The dripping time of the copper ion solution was 110 minutes. The reactor was placed in a microwave heating device with a frequency of 2500MHz and a power of 1000W, the heating temperature was 40℃, and the heating time was 6 hours. In the middle thin film controlled reaction zone, the interface of the two solutions controlled slow contact, reacted, and generated blue suspended solids.
[0071] The solution after the reaction was centrifuged to separate the solid and liquid, and then washed with N,N-dimethylformamide for 3 times and chloroform for 3 times. After drying in air atmosphere at 80° C. for 24 hours, CuBDC nanosheets were obtained with a yield of 75%.
[0072] SEM characterization shows that the single-layer nanosheets have uniform size, length of 4-6 μm, thickness of about 15 nm, aspect ratio of 266-400, and BET specific surface area of 630 m 2 / g.
[0073] Comparative Example 1
[0074] 0.5 g of copper nitrate was added to a mixed solvent of 15 g of N,N-dimethylformamide and 45 g of acetonitrile to prepare a copper ion solution.
[0075] The ligand solution was prepared by adding 0.5 g of terephthalic acid to a mixed reagent of 45 g of N,N-dimethylformamide and 15 g of acetonitrile.
[0076] According to the mass ratio of copper ion solution to ligand solution of 1:1, the copper ion solution was poured into the ligand solution and mixed evenly, and the reaction solution was placed in a microwave heating device with a frequency of 2500 MHz and a power of 500 W. The heating temperature was 55° C. and the heating time was 6 hours. A reaction occurred to generate a blue suspended solid.
[0077] The solution after the reaction was centrifuged to separate the solid and liquid, and then washed with N,N-dimethylformamide for 3 times and chloroform for 3 times. After vacuum drying at 80°C for 18 hours, CuBDC nanosheets were obtained with a yield of 47 wt%.
[0078] Nanosheets are multi-layer stacked two-dimensional nanosheet materials. The length of the nanosheet is 1 μm, the thickness is about 60-80 nm, the aspect ratio is 12-17, and the BET specific surface area is 490 m 2 / g.
[0079] Comparing Comparative Example 1 with Example 1, it can be seen that the present invention uses a thin film controlled reactor to obtain two-dimensional nanosheets with a higher aspect ratio and a larger specific surface area, and the CuBDC yield is also improved.
[0080] Application Examples
[0081] The materials prepared in the above examples were assembled into batteries for constant current charge and discharge tests. The test conditions were: current density 5000 mA / g, 100 cycles, and the test results are shown in Table 1.
[0082] The materials prepared in the above examples were doped with polyimide polymer (recorded as comparative example 2) to prepare gas separation membrane materials for gas separation tests. The test conditions were: separation of a mixed gas with a volume ratio of CO2:CH4 of 1:1, pressure of 4 bar, temperature of 35°C, and a CuBDC nanosheet loading of 10 wt%. The test results are shown in Table 2.
[0083] Table 1 Test results of 100 cycles
[0084]
[0085]
[0086] Table 2 Separation test results
[0087] <![CDATA[CO2 / CH4 selectivity]]> <![CDATA[CO2 permeability (unit: Barrer)]]> Example 1 25.8 120 Example 2 25.4 124 Example 3 26.7 118 Example 4 26.1 119 Comparative Example 1 17.9 101 Comparative Example 2 20.2 100
Claims
1. A CuBDC nanosheet, which is a single-layer two-dimensional CuBDC nanosheet material; the aspect ratio of the CuBDC nanosheet is 80 to 400.
2. The CuBDC nanosheet according to claim 1, characterized in that: The specific surface area of the CuBDC nanosheet is 580-630 m 2 / g.
3. The CuBDC nanosheet according to claim 1 or 2, characterized in that: The aspect ratio of the CuBDC nanosheet is 100-300.
4. The CuBDC nanosheet according to claim 1, characterized in that: The length of the CuBDC nanosheet is 2-6 μm, preferably 4-5 μm, and the thickness is 15-25 nm, preferably 18-22 nm.
5. A method for preparing the CuBDC nanosheet according to any one of claims 1 to 4, comprising: (1) The method adopts a thin film reactor; a thin film component is provided in the thin film reactor, and the reactor is divided into an upper region and a lower region by the thin film component; The film component is provided with holes; (2) placing a copper ion solution in the upper region of a thin film reactor; The ligand solution is placed in the lower region of the thin film reactor; the copper ion solution is dripped into the ligand solution through the holes of the thin film component, and a reaction occurs in the lower region of the reactor, and the CuBDC nanosheets are obtained after separation.
6. The preparation method according to claim 5, characterized in that: In step (1), the pore size of the pores on the film component is 3 to 5 μm; the porosity is 80 to 90%; more preferably, the pore thickness is 30 to 60 μm.
7. The preparation method according to claim 5, characterized in that: In step (2), the copper ion solution includes inorganic copper salt, N,N-dimethylformamide and acetonitrile; further, based on the mass of the copper ion solution, the copper ion solution includes: 0.8% to 1.5% inorganic copper salt, 22% to 27% N,N-dimethylformamide, and 72% to 77% acetonitrile.
8. The preparation method according to claim 5, characterized in that: In step (2), the ligand solution includes terephthalic acid, N,N-dimethylformamide and acetonitrile; further, based on the mass of the ligand solution, the ligand solution includes: 0.8% to 1.5% terephthalic acid, 72% to 77% N,N-dimethylformamide, and 22% to 27% acetonitrile.
9. The preparation method according to claim 5, characterized in that: In step (2), the mass ratio of the copper ion solution to the ligand solution is 0.8 to 1.
2.
10. The preparation method according to claim 5, characterized in that: In step (2), the copper ion solution is added dropwise for 100 to 120 minutes.
11. The preparation method according to claim 5, characterized in that: In step (2), the reaction is carried out under microwave heating; the microwave heating temperature is 40 to 55° C. and the time is 3 to 6 h.
12. Use of the CuBDC nanosheet according to any one of claims 1 to 4 or the CuBDC nanosheet prepared by the preparation method according to any one of claims 5 to 11 in the fields of gas storage, adsorption separation, heterogeneous catalysis, electrochemistry or analysis.
Citation Information
Patent Citations
Metal-organic framework material CuBDC nanosheets, their preparation methods and applications
CN106252663B
Preparation method for back-diffusion in-situ self-assembled MOFs nanofiltration membrane
CN105126638A
Metal organic framework nanosheet, preparation method, working electrode and sensor
CN115109262A
Ultrathin defect-free ZIFs-GO composite membrane, preparation method and application thereof
CN116371213A
Ultrathin double-ligand two-dimensional MOF nanosheet film as well as preparation method and application thereof
CN116422162A